The D-Stem in Western Semitic - Ryder, Stuart Austin (1966)
Ph. D.; University Microfilms Order No. 66-14,995. Microfilm $3.40; Xerography $11.95. — See: Dissertation Abstracts 27/9 (Ann Arbor, Mich., March 1967) 3026A.